Marker cluster rigidity in a multi-segment foot model - Chan, P; Stebbins, J; Zavatsky, A (Elsevier, 2019)
Multi-segment foot models (MSFM) are used in gait analysis for the diagnosis and planning of treatment for patients with foot deformities. Like other biomechanical models, MSFMs represent the leg and foot as a series of linked rigid segments, but such a simplification may not be appropriate, particularly for the flexible forefoot. This study investigated the appropriateness of the rigid body assumption on marker clusters used to define the individual segments (tibia, hindfoot, forefoot) of a widely-used MSFM. Rigidity of the marker clusters was quantified using the rigid body error () calculated for each frame of a representative gait cycle for 64 normal healthy adults who underwent gait analysis. is a measure of how well the tracking marker configuration at each frame compares to the arrangement of the same markers in a reference pose. As expected, the patterns of deformation of the three marker clusters differed over the gait cycle. The hindfoot cluster remained relatively undeformed in comparison to the forefoot and tibia clusters. The largest deformations of the forefoot cluster occurred near the beginning and end of the stance phase. The tibia cluster deformed throughout the entire gait cycle, with a pattern similar to that of a typical knee flexion angle graph. The results raise questions about the appropriateness of the rigid-body assumption when applied to MSFMs, particularly in the forefoot region.